(untitled) (Northern International Medical College Journal, 2015)
Objective : To determine the efficacy of oral prednisolone among children with acute bronchiolitis who have associated family history of atopy. Materials and Methods : This randomized double blind placebo controlled trial was carried out in Dhaka Medical College Hospital during July08 to June10. A total of sixty patients (1-24 months) of acute bronchiolitis who had family history of atopy (e.g. allergic rhinitis, allergic conjunctivitis, asthma, eczema) were enrolled. After enrollment, allocation of either prednisolone or placebo to the study subjects were done randomly by lottery method and the researcher remained blind about the allocation. Finally 30 cases received prednisoloneorally at a dose of 2mg/kg/day 8 hourly for 3 consecutive days and 30 cases received placebo (made of flour). In addition, both the groups got same supportive measures. During intervention, study subjects were monitored by Modified Respiratory Distress Assessment Instrument (MRDAI) score twice daily for consecutive 3 days. Duration of oxygen therapy as well as length of hospital stay was also determined. Data were analyzed using appropriate statistical tests and a p value of <0.05 was considered significant. Results : The respiratory rate, accessory muscle use and auscultatory finding scores were significantly declined in Prednisolone group than the placebo group (p<.05). However, cyanosis score though declined in both groups, the difference was not significant (p>.05). Mean duration of oxygen therapy needed in Prednisolone group was significantly lesser than the placebo group (13.7 vs 24.1 hours; P<.01). Similarly, the length of hospital stay was shorter in prednisolone group than in placebo group (3.3 vs 4.6days; p<.01). Conclusions : Three days of oral prednisolone therapy along with supportive measures was found to be significantly useful among children with acute bronchiolitis having family history of atopy in terms of clinical recovery, oxygen requirement and duration of hospital stay Northern International Medical College Journal Vol.6(1) 2014: 9-11